Implementing and optimizing a communication curriculum in medical teaching: Stakeholders’ perspectives - Brünahl, Christian Andreas; Hinding, Barbara; Eilers, Leonie; Höck, Jennifer; Hollinderbäumer, Anke; Buggenhagen, Holger; Reschke, Kirsten; Schultz, Jobst-Hendrik; Jünger, Jana (PLOS ONE, 2022)
Objective The relevance of communication in medical education is continuously increasing. At the Medical Faculty of Hamburg, the communication curriculum was further developed and optimized during this project. This article aims to describe the stakeholders’ perceived challenges and supporting factors in the implementation and optimization processes. Methods The initial communication curriculum and its development after a one-year optimization process were assessed with a curricular mapping. A SWOT analysis and group discussions were carried out to provide information on the need for optimization and on challenges the different stakeholders faced. Results The curricular mapping showed that the communication curriculum is comprehensive, coherent, integrated and longitudinal. In both the implementation and the project-related optimization processes, support from the dean, cooperation among all stakeholders and structural prerequisites were deemed the most critical factors for successfully integrating communication content into the curriculum. Conclusion The initiative and support of all stakeholders, including the dean, teachers and students, were crucial for the project’s success. Practice implications Although the implementation of a communication curriculum is recommended for all medical faculties, their actual implementation processes may differ. In a “top-down” and “bottom-up” approach, all stakeholders should be continuously involved in the process to ensure successful integration.